2022
DOI: 10.3390/cimb44020047
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mutations and Overexpression in the CYP51A and B Genes Lead to Decreased Sensitivity of Venturia effusa to Tebuconazole

Abstract: Multiple demethylation-inhibiting (DMI) fungicides are used to control pecan scab, caused by Venturia effusa. To compare the efficacy of various DMI fungicides on V. effusa, field trials were conducted at multiple locations applying fungicides to individual pecan terminals. In vitro assays were conducted to test the sensitivity of V. effusa isolates from multiple locations to various concentrations of tebuconazole. Both studies confirmed high levels of resistance to tebuconazole. To investigate the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The inhibition rate of tebuconazole, myclobutanil and propiconazole was all increased in ΔSsStuA (Figure 3A,B), and the expression level of SsStuA also increased under tebuconazole treatment (Figure 3C). CYP51 is the target of tebuconazole [38,39], therefore, the expression of SsCYP51 was measured in WT and ΔSsStuA. The results showed that SsCYP51 was upregulated in ΔSsStuA, which indicate that SsCYP51 is not the only target of tebuconazole in S. sclerotiorum (Figure 3D).…”
Section: δSsstua Is Sensitive To Tebuconazolementioning
confidence: 99%
“…The inhibition rate of tebuconazole, myclobutanil and propiconazole was all increased in ΔSsStuA (Figure 3A,B), and the expression level of SsStuA also increased under tebuconazole treatment (Figure 3C). CYP51 is the target of tebuconazole [38,39], therefore, the expression of SsCYP51 was measured in WT and ΔSsStuA. The results showed that SsCYP51 was upregulated in ΔSsStuA, which indicate that SsCYP51 is not the only target of tebuconazole in S. sclerotiorum (Figure 3D).…”
Section: δSsstua Is Sensitive To Tebuconazolementioning
confidence: 99%